Preparation and properties of borate glass coatings on Ti-based alloy substrates - 朱冬梅 娄霞 罗发 熊良明 周万城 (Transactions of Nonferrous Metals Society of China, 2007)
A series of BaO-La2O3-B2O3 （BLB） glass coats on the Ti-based alloy substrates were developed at different temperatures for different times. The BLB glasses were analyzed by differential thermal analysis （DTA） and thermal mechanical analysis （TMA） to determine the crystallization temperature and coefficients of thermal expansion （CETs） of the glass. The tensile strength and microstructure of the glass coats were analyzed and the effects of the coating condition on the tensile strength and microstructure were discussed. The results show that the CETs of the borate glass at different temperatures match with those of Ti-based alloy, and the difference between the borate glass and Ti-based alloy at each temperature is below 5%. The spreading area in N2 atmosphere is much larger than that in air atmosphere, indicating that N2 atmosphere is helpful for the wetting of borate glass to Ti-based alloy. The tensile strength of the glass coats can reach as high as 28.42 MPa, meeting the requirements for the coat binder. With the increase of coating time, the tensile strength of coats increases firstly while then decreases. The coat prepared at 730 ℃ for 30 min is fairly smooth and complete, while the other coats contain lots of defects such as large or small uncoated region. It is believed that the coating temperature of 730℃ and coating time of 30 min are the proper coating conditions to prepare BLB glass coats.